Lifetime Multiple Mild Traumatic Brain Injuries Are Associated with Cognitive and Mood Symptoms in Young Healthy College Students - Vynorius, Kyle C.; Paquin, Alyssa M.; Seichepine, Daniel R. (Frontiers in Neurology, 2016)
Background/objectives Repetitive mild traumatic brain injury (mTBI, also known as concussion) has been associated with a range of long-term mood and cognitive deficits, including executive dysfunction. Previous research in athletes suggests that cognitive and mood problems are associated with a history of repetitive mTBI. However, to date, no studies have examined the impact of a lifetime accumulation of repetitive mTBIs on cognition, particularly executive functioning, and mood in a sample of young adults who were not athletes. Therefore, the present study looked at potential effects of repetitive mTBIs on self-reported cognitive complaints, executive functioning, and mood in young adults. Methods Eighty-four total students responded, and 26 of those were excluded from analyses due to reporting only 1 mTBI. The final sample consisted of 58 healthy young adults (mean age = 22.84, STD = 4.88) who completed the Cognitive Complaint Index (CCI), the Behavior Rating Inventory of Executive Function, adult version (BRIEF-A), and the Beck Depression Inventory, second edition (BDI-II). Twenty-nine participants denied having an mTBI history, and 29 reported 2 or more lifetime mTBIs (range 2–7). Results Young otherwise healthy adults with a lifetime history of repetitive mTBI compared to those that reported no history of mTBI reported more change in cognitive functioning over the past 5 years, worse executive functioning, and more symptoms of depression. As the number of lifetime mTBIs increased, scores on the CCI, BRIEF-A, and BDI-II also increased, indicating worse functioning. Conclusion These findings suggest that a lifetime accumulation of two or more mTBIs as compared to a history of no reported mTBIs may result in worse cognitive functioning and symptoms of depression in young adults.